Transfer of More Than Two Embryos, Regardless of the Age of the Female Partner, Is Not Beneficial for Neither the Mothers nor the Babies: Lessons from the Latin American Registry of Assisted Reproductive Techniques - Schwarze-Meza, J (SBRA - Associação Brasileira de Reprodução Assistida (Brazilian Society of Assisted Reproduction), 2017)
Objective: ART has helped millions of infertile couples worldwide to overcome their childlessness. These successes have been accompanied by an increase in multiple deliveries, and perinatal complications associated. The explanation for this complication is the transfer of more than one embryo, to increase the odds of delivery. Our objective was to compare the outcome of elective dual embryo transfer (eDET) to that of the transfer of more than two embryos without embryo cryopreservation (TET), terms of delivery rate and multiple delivery. Methods: We analyzed the data registered by 155 clinics members of the RLA: 11,024 eDET and 10,634 TET. Results: The delivery rate was significantly higher when eDET was performed than when TET was performed (40.24% and 26.98%, p < 0.001). Also, the ratio of twin deliveries was higher in eDET (25.80% and 20.56%, p < 0.001). However, the ratio of triplets and more deliveries was higher in TET than in eDET (2.34%and 0.52%, p < 0.001). These findings were consistent across the different age categories of the female partner. Conclusion: Our findings suggest that eDET was associated with a statistically significant better delivery rate per embryo transfer, and lower ratio of triplet-and-higher deliveries, regardless of the woman’s age. Therefore, there is no evidence that supports the transfer of more than two embryos. © 2017, Sociedade Brasileira de Reproducao Assistida. All rights reserved.